Comparison Air Temperature under Global Climate Change Issue in Gifu city and Ogaki city, Japan - Ali Rahmat; Abdul Mutolib (Indonesian Journal of Science and Technology, 2016)
Increases in air temperature indicate a global climate change. Thus, information in the change of temperature regional scale is important to support global data. The present research was conducted in Gifu city and Ogaki city located in Gifu prefecture, Japan. The results showed that, average air temperatures in both cities are quite similar with a difference value of under 1oC. Maximum air temperature in Gifu city is significantly higher than Ogaki city, whereas minimum air temperature in Gifu city is significantly lower than in Ogaki city. Daily range of air temperature in Gifu city significantly higher than in Ogaki city. In both cities, air temperature relatively increased in three decades. This is because of different in land characteristics in both cities.